1996
DOI: 10.1046/j.1365-2141.1996.d01-1811.x
|View full text |Cite
|
Sign up to set email alerts
|

A plasmocyte selective monoclonal antibody (B‐B4) recognizes syndecan‐1

Abstract: We developed a new monoclonal antibody. B-B4, which specifically identifies human plasma cells. It strongly reacts with all multiple myeloma cell lines and with malignant plasma cells of all tumour samples of the multiple myeloma patients tested. B-B4 does not react with any peripheral blood, bone marrow or tonsil cells. Cloning of the B-B4 antigen reveals that the monoclonal antibody recognizes syndecan-1. It appears that the monoclonal antibody B-B4 is a suitable marker for human plasmocyte identification am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
216
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(230 citation statements)
references
References 13 publications
11
216
0
1
Order By: Relevance
“…In agreement with previous studies, all of the plasmablastic lymphoma cases in this study had a post-germinal center B-cell/plasma cell phenotype, expressing MUM1/IRF4 and CD138/syndecan-1, but negative for CD20. 3,[20][21][22] Furthermore, we observed that several markers that may be aberrantly expressed in plasma cell neoplasms, CD56, CD10 and CD4, were also expressed in most cases of plasmablastic lymphoma. CD56 and CD10, markers frequently expressed in plasma cell myeloma, [23][24][25] were positive in 5/9 and in 6/9 of the plasmablastic lymphoma cases in our series, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…In agreement with previous studies, all of the plasmablastic lymphoma cases in this study had a post-germinal center B-cell/plasma cell phenotype, expressing MUM1/IRF4 and CD138/syndecan-1, but negative for CD20. 3,[20][21][22] Furthermore, we observed that several markers that may be aberrantly expressed in plasma cell neoplasms, CD56, CD10 and CD4, were also expressed in most cases of plasmablastic lymphoma. CD56 and CD10, markers frequently expressed in plasma cell myeloma, [23][24][25] were positive in 5/9 and in 6/9 of the plasmablastic lymphoma cases in our series, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…CD138, also known as Syndecan-1, is expressed on plasma cells, but not on circulating B cells, T cells or monocytes. 25 The purity of plasma cells obtained by this method was more than 90%, as confirmed by flow cytometry (FAC sort: Becton Dickinson, San José, CA, USA) using the Paint a Gate program. Plasma cell leukaemia was not purified.…”
Section: Human Tissue Samplesmentioning
confidence: 84%
“…Syndecan-1 immunohistochemistry is specific for plasma cells. It is a reliable marker for quantifying plasma cells in paraffin-embedded bone marrow biopsy specimens (5,6). It has also been noted to stain plasma cells in routine paraffinembedded skin biopsy sections (Bayer-Garner and Smoller, unpublished observation).…”
Section: Discussionmentioning
confidence: 96%
“…The endogenous peroxidase activity was quenched with 0.3% peroxidase and nonspecific binding was quenched with horse serum block (Oncogene Research Products, Cambridge, MA). The DAKO Large Volume LSAB2 Alkaline Phosphatase Kit (DAKO) was used with 1:100 dilution of B-B4 (Serotec, Raleigh, NC), a mouse anti-human antibody that recognizes an epitope of human syndecan-1 (CD138) (5). Sections were incubated with biotinylated secondary antibody for thirty minutes, and then with streptavidin alkaline phosphatase for thirty minutes.…”
Section: Methodsmentioning
confidence: 99%